119k views
1 vote
Please help me out with this

Please help me out with this-example-1

1 Answer

5 votes

Answer:

a + 5b

Explanation:

Distributive property:

a*(b + c) = a*b + a*c

3*(a + b). In this multiply each term with 3 and in -2(a- b), multiply each term with (-2).

3*(a +b) - 2*(a - b) = 3*a + 3*b + (-2)*a + (-2)*(-b)

= 3a + 3b - 2a + 2b

= 3a - 2a + 3b + 2b {Combine like terms}

= a + 5b

Like terms have same variable with same power. Here, 3a and (-2a) are like terms. So, combine the coefficients of the like terms

3a + (-2a) = a.

User Marvin Herbold
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.